Inovasi Pupuk Cocopeat dan Pemberdayaan Masyarakat melalui Program KKN Kolaboratif di Desa Ranulogong - Moh Amirul Hamzah; Elsa Margaretha; Nurhalisa Putri; Ika Bela Nuradinda; Dyyah Ayu Laksmy; Wanda Nirmalasari; Erika Novembriana; Diana Fajriah Kusuma Afanto; Muhammad Roziqin; Evi Puji Lestari; Umi Nurjanah; Yohana Maria Penga (Dental Agromedis, 2025)
The village of Ranulogong in the Randuagung District, Lumajang, has significant agricultural potential but is constrained by low water discharge during the dry season, which often leads to crop failure. On the other hand, the abundant coconut husk waste has not been optimally utilized. This Collaborative Community Service Program (KKN) aims to design and prepare a sustainable agricultural solution model through an innovative organic fertilizer made from cocopeat (coconut coir dust) mixed with chicken manure to increase soil water retention capacity. The program's implementation methods included: 1) The development of the cocopeat fertilizer product;2) The creation of a demonstration plot (demplot) as a proof of concept; 3) The production of educational media in the form of brochures and video tutorials for independent knowledge transfer; and 4) Community service programs in education at the elementary (SD) and early childhood education (PAUD) levels. The results of the activities showed the successful development of a ready- to-implement cocopeat fertilizer product and demonstrated its potential in maintaining soil moisture through the demonstration plot. Educational media were also produced and handed over to the village as a sustainable knowledge asset. The education programs at the elementary and early childhood levels proceeded as planned and succeeded in raising awareness of the importance of continuing education and in training the creativity of young children. This program successfully developed a foundation for sustainable agricultural solutions while also empowering the educational aspects in Ranulogong village.Keywords: Cocopeat, community empowerment, KKN (Student Community Service), sustainable agriculture, children's education